(untitled) (Journal of Economic Research & Business Administration, 2017)
The companies permanently perform calculations with the suppliers for purchased production goods, raw material and other material assets, executed works and rendered services and subcontractors for executed works and work stages. Calculation debts during financial and economic activities shall be within accepted value. Timely taking the measures is possible only in systematic control execution by the company. The analysis of credit debt, which means not only debt to the supplier, but credits, loans, calculations with budget and other liabilities, take an important place. Analysis of debt by the terms of extinction of obligations is important. Generally, herewith the debt is divided into two large groups: long-term and short-term. The aim of the obligation analysis of the suppliers and subcontracts is to appraise status of obligations of the suppliers and subcontracts and to outline method of their improvement. Carried out examination is based on studying of practice of the companies’ activities.